Terrorism, Dynamic Commitment Problems, and Military Conflict. Issue 2 (5th October 2015) - Bapat, Navin A.; Zeigler, Sean
Abstract: Since 9/11, several states have initiated military conflicts in the name of fighting terrorism. However, studies indicate that the costs of terrorism are insignificant compared to the damage created by war. This raises the question: Why do states initiate costly wars when the risk posed by terrorism appears marginal? This study presents two explanations. First, we argue that while terrorists frequently fail to achieve their strategic objectives, terrorists can accomplish tactical objectives and may transition to insurgencies by seizing control of pockets of territory. States may respond by initiating preventive wars to stop terrorists from consolidating control over their strategically valuable territories (e.g., resource‐rich areas). Second, rival states may opportunistically exploit terrorist violence by declaring that the government is a "weak state." This allows rivals to seize portions of the government's territory under the cover of fighting terror. We test these hypotheses using post–Cold War African dyads from 1990 to 2006.